THE EFFECT OF CREATIVE PROJECT LEARNING OUTCOMES AND ENTREPRENEURSHIP ON ENTREPRENEURIAL INTEREST THROUGH INTERNAL LOCUS OF CONTROL - Musyarofah, Ina Nur Aini; Wulandari, Siti Sri; Bin Mohd Diah, Mohd Lizam (Jurnal Pendidikan Ilmu Sosial, 2024)
This research seeks to examine how creative project-based learning outcomes and entrepreneurial activities influence students’ interest in entrepreneurial activities influence students’ interest in entrepreneurship by considering their internal locus of control at SMK Negeri 1 Surabaya. The research method used is quantitative with the type of explanatory research. Data collection using questionnaires and analysis using Partial Least Square (PLS-SEM) with path analysis using SmartPLS 3.0 software the population was 160 students in class XI of the office management skills program with a sample size of 110 students who had taken Creative and Entrepreneurial Projects (PKK) according to independent criteria. The results showed that PKK learning outcomes have there is constructive correlation, albeit not statistically significant to entrepreneurial interest. PKK learning outcomes have a positive relationship, but not significant to the internal locus of control. The internal locus of control strongly correlates with entrepreneurial interest in a meaningful way. Internal locus of control cannot mediate the relationship between PKK learning outcomes with entrepreneurial interest.